The Correlation Between English Club Participation and Student English Learning Achievement at MAN 2 Kebumen - Makhasina, Ibtida Atul; Heriyanto, Dwi (UM Purwokerto Press, 2025)
This study analyses the correlation between participation in English Club participation and student English learning achievement at MAN 2 Kebumen. This study aims to determine the relationship between student participation in extracurricular English Club and student learning achievement. This research is a quantitative research with correlation method. The population of this study was grade XI students of MAN 2 Kebumen with a sample of grade XI selected using purposive sampling technique for sample selection because the target sample taken was students who participated in the English Club. The research data were selected by using two instruments; questionnaire and documentation data. The researcher used a closed questionnaire with the respondent choosing the answer 'yes or no' with the documents used being student learning outcomes. The questionnaire was distributed to students who are members of the English Club. Then the results were analyzed by calculation using the Spearman correlation analysis method using SPSS software with a significance level, the author obtained a significant correlation of 0.008. The result is 0.008 < 0.05. Since 0.008 is smaller than 0.005 (0.008 < 0.05), this means that there is a relationship between student participation in tutoring and the variable of student English learning achievement. Furthermore, from the data analysis, a spearman correlation of 0.621 was found, which means that the correlation is strong according to the correlation interpretation table. Based on the research results, the null hypothesis is rejected. The analysis showed a significant positive correlation between students' involvement in English Club and their English learning achievement. This finding indicates that involvement in language-based extracurricular activities can support students' academic achievement in English learning.